ANALISIS PENGARUH INDEKS PEMBANGUNAN MANUSIA (IPM) TERHADAP KEMISKINAN DI PROVINSI DKI JAKARTA - Novita Ramdhani; Yulia Anggraeni; Deris Desmawan (Jurnal Ekonomi, Bisnis dan Manajemen, 2022)
Based on the fundamental aspects of people's living standards, the measure of progress in human development is called the Human Development Index. As the basis for the development structure of a region, the Human Development Index (HDI) is the most significant benchmark or parameter. The purpose of this study is undoubtedly to ascertain whether poverty in DKI Jakarta Province is influenced by the Human Development Index (IPM) variable. To achieve the research objectives, tests were conducted using simple regression analysis and quantitative techniques. The test results show that poverty in DKI Jakarta Province is significantly affected by the Human Development Index (HDI) because the significance value is less than 0.05. Because the value of determination, or R2, is close to 1, and some of the other influence values are influenced by other variables that have not been analyzed or researched, the value of the results of the Variable Human Development Index (HDI) test has a strong positive influence on poverty in DKI Jakarta Province.